ANTI-CRISIS POLICIES IN THE AGE OF GLOBAL CRISIS - THE EXPERIENCES OF THE COVID-19 PANDEMIC - Živanović, Cvijetin; Šantić, Nataša; Duraković, Besim (ACADEMIC REVIEW, 2023)
This paper is an effort made by the authors to point out some proposals of international organizations, corporations, representatives of the academic sector, and even state authorities regarding global, regional and national anti-crisis policies in the world crises circumstances. In this connection, the lack of will on the part of the developed part of the international community to implement economic recovery after the pandemic by solving the climate and ecological crisis and providing support to the green industry was emphasized. Also, numerous anti-crisis proposals of the international community ignore the exceptional role of the digital sector of the economy, although it has enabled the world to minimize the negative economic consequences of the COVID-19 pandemic in the short term through the partial or complete transition of most processes on the Internet, in corporations, universities and schools, emphasizing the importance of inclusiveness and fairness in overcoming the world crisis, as well as the need to put individuals and communities, not corporations, at the center of recovery policies.